Adhesive hydrogel wrap loaded with Netrin-1-modified adipose-derived stem cells: An effective approach against periarterial inflammation after endovascular intervention - Jiang, Yihong; Cai, Yuting; Hu, Jiateng; Zhang, Xing; Lei, Jiahao; Peng, Zhaoxi; Huang, Qun; Xu, Zhijue; Li, Bo; Qin, Jinbao; Li, Weimin; Sun, Dazhi; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Endovascular interventions, such as balloon dilation and stent implantation, are currently recommended as the primary treatment for patients with peripheral artery disease (PAD), greatly improving patient prognosis. However, the consequent lumen restenosis that occurs after endovascular interventions has become an important clinical problem. Inflammation has been proven to be crucial to postoperative restenosis. In previous studies we have identified that Netrin-1-modified adipose-derived stem cells (N-ADSCs) transplantation is an effective anti-inflammatory strategy to repair vascular damage. Nevertheless, it remained to be explored how one could constantly deliver N-ADSCs onto damaged arteries. Therefore, we developed an adhesive double network (DN) hydrogel wrap loaded with N-ADSCs for sustained perivascular delivery. Inspired by the adhesion mechanism of mussels, we developed an adhesive and tough polyacrylamide/calcium-alginate/reduced graphene oxide/polydopamine (PAM/CA/rGO/PDA) hydrogel. Dopamine was attached to graphene sheets and limitedly oxidized to generate free catechol groups. The hydrogel could wrap damaged arteries and induce anti-inflammatory effects through N-ADSCs. In vitro experiments demonstrated that N-ADSCs significantly promoted the M2 polarization of macrophages to anti-inflammatory phenotypes and reduced the expression of inflammatory factors. In vivo experiments in a rat carotid artery guidewire injury model showed that the adhesive hydrogel wrap loaded with N-ADSCs could significantly reduce arterial inflammation, inhibit intimal hyperplasia and improve re-endothelialization. Altogether, this newly developed N-ADSCs-loaded hydrogel wrap provides an effective slow-releasing system, which may be a promising way to prevent and treat restenosis after endovascular interventions.